Prospects for a Monetary Union in the East Africa Community: Some Empirical Evidence - Guglielmo Maria Caporale; Hector Carcel; Luis A. Gil-Ala\~na (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines G-PPP and business cycle synchronization in the East Africa Community with the aim of assessing the prospects for a monetary union. The univariate fractional integration analysis shows that the individual series exhibit unit roots and are highly persistent. The fractional bivariate cointegration tests (see Marinucci and Robinson, 2001) suggest that there exist bivariate fractional cointegrating relationships between the exchange rate of the Tanzanian shilling and those of the other EAC countries, and also between the exchange rates of the Rwandan franc, the Burundian franc and the Ugandan shilling. The FCVAR results (see Johansen and Nielsen, 2012) imply the existence of a single cointegrating relationship between the exchange rates of the EAC countries. On the whole, there is evidence in favour of G-PPP. In addition, there appears to be a high degree of business cycle synchronization between these economies. On both grounds, one can argue that a monetary union should be feasible.
Keywords: C22; C32; F33; 330; East Africa Community; monetary union; optimal currency areas; fractional integration and cointegration; business cycle synchronization; Hodrick-Prescott filter